Interrelations Between Process Safety Management Elements - Mohd Shariff, Azmi (2017)
OSHA PSM standard has been established with 14 ele- ments that define the management principles to control pro- cess hazards and protect the workplace. One of the key factors to the success of Process Safety Management (PSM) implementation is that each element comes as a component in an integrated PSM program